Immunogenicity and Safety of One-Dose Human Papillomavirus Vaccine Compared With Two or Three Doses in Tanzanian Girls (DoRIS): An Open-Label, Randomised, Non-inferiority Trial. Issue 3 (March 2023) - Watson-Jones, Deborah; Changalucha, John; Whitworth, Hilary; Pinto, Ligia; Mutani, Paul; Indangasi, Jackton; Kemp, Troy; Hashim, Ramadhan; Kamala, Beatrice; Wiggins, Rebecca; Songoro, Twaib; Connor, Nicholas; et al.
ABSTRACT: The global burden of cervical cancer remains very high, with more than 340, 000 potentially preventable deaths annually and disproportionally affects low-income and middle-income countries. Countries that have adopted HPV vaccination administer a multidose schedule with 2 doses offered to girls younger than 15 years, and 3 offered to girls 15 years and older or immunocompromised individuals. Unfortunately, several barriers to full immunization remain, and only 15% of girls in the target age group worldwide are estimated to be fully vaccinated. A single-dose vaccine would remove many barriers and be significantly cheaper; however, evidence is needed on the immunogenicity and efficacy. This randomized phase 3 clinical trial (DoRIS) aimed to examine immune responses after a single dose of HPV vaccine in the target age group for HPV vaccination in Tanzania. Girls aged 9–14 years who have not been vaccinated for HPV and did not have any history of cervical lesions, treatment for positive cervical cancer screening, or immunocompromised status were invited from Government schools to participate. Participants were randomized to 1 of 6 arms comprising 3 different dose schedules of 2 different HPV vaccines (3 doses over 6 months, 2 doses given 6 months apart, or a single dose for either the 2-valent vaccine or the 9-valent vaccine). Blood samples were collected for immunological assays at 1, 7, 12, and 24 months after vaccination. The primary study outcome was noninferiority of HPV 16 and HPV 18 specific seropositivity after a single dose compared with 2 or 3 doses of the same vaccine 24 months after vaccination. Primary analyses were undertaken in the per-protocol population, including those who received the allocated doses of HPV vaccine in the protocol-defined window. A sensitivity analysis included all participants who received at least 1 dose of HPV vaccine. A total of 930 girls were enrolled and randomized with 155 participants per group. At 24 months, 856 (93%) girls were included in the per-protocol analysis of anti-HPV 16 antibody responses, and 831 (91%) in the per-protocol analysis of anti-HPV 18. All but 2 participants were seropositive for HPV 16 IgG at 24 months (1 participant in each of the 1-dose arms was not), and all but 6 participants were HPV 18 seropositive at 24 months (2 in the 1-dose 2-valent group, 3 in the 1-dose 9-valent group, and 1 in the 3-dose 9-valent group). Noninferiority of HPV 16 seroconversion was met at 24 months for 1 dose compared with 2 doses or 3 doses for both vaccines; however, noninferiority for HPV 18 seroconversion was not met despite 98% of girls in the 1-dose arms of both vaccines testing positive for anti-HPV 18. There was no difference in serious adverse events among study groups or any serious adverse events related to the vaccine. The results of this study demonstrate that, in healthy Tanzanian girls, a single dose of the 2-valent or 9-valent HPV vaccines was well tolerated and resulted in high seropositivity and induced stable vaccine responses that persisted to 24 months.